Improving the use of research evidence in guideline development: 4. Managing conflicts of interests - Boyd, Elizabeth A (BioMed Central, 2006)
BACKGROUND: The World Health Organization (WHO), like many other organisations around the world, has recognised the need to use more rigorous processes to ensure that health care recommendations are informed by the best available research evidence. This is the fourth of a series of 16 reviews that have been prepared as background for advice from the WHO Advisory Committee on Health Research to WHO on how to achieve this. OBJECTIVES: We reviewed the literature on conflicts of interest to answer the following questions: 1. What is the best way to obtain complete and accurate disclosures on financial ties and other competing interests? 2. How to determine when a disclosed financial tie or other competing interest constitutes a conflict of interest? 3. When a conflict of interest is identified, how should the conflict be managed? 4. How could conflict of interest policies be enforced? METHODS: We searched PubMed, the Cochrane Methodology Register and selectively searched for the published policies of several organizations, We did not conduct systematic reviews ourselves. Our conclusions are based on the available evidence, consideration of what WHO and other organisations are doing and logical arguments. KEY QUESTIONS AND ANSWERS: What is the best way to obtain complete and accurate disclosures on financial ties and other competing interests? • Although there is little empirical evidence to guide the development of disclosure forms, minimal or open-ended formats are likely to be uninformative. We recommend the development of specific, detailed, structured forms that solicit as much information as possible about the nature and extent of the competing interests. How to determine when a disclosed financial tie or other competing interest constitutes a conflict of interest? • There is no empirical evidence to suggest that explicit criteria are preferable to ad hoc committee decisions when deciding if a disclosed financial tie is a conflict of interest. However, explicit criteria may make decision-making easier. When a conflict of interest is identified, how should the conflict be managed? • Descriptive studies suggest that appropriate management strategies are best determined on a case-by-case basis. Thus, WHO should use a wide range of management strategies to address disclosed conflicts of interest, with public disclosure of conflicts associated with each meeting as a minimum and recusal of conflicted individuals as the other extreme. How could conflict of interest policies be enforced? • Although there are no empirical studies of the enforcement of conflict if interest policies, descriptive studies of other organizations and institutions suggest that WHO convene a standing committee to review all financial disclosure statements prior to the commencement of committee meetings/hearings and to make management recommendations when necessary. A standard policy requiring all financial ties to be made public (i.e., recorded into the meeting minutes) should reduce the number of problematic cases. In instances where the conflicts seem intractable, a recommendation of recusal may be necessary to protect the greater interests of WHO and its constituents.